2021
DOI: 10.1029/2020wr028343
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Local and Nonlocal Factors on Soil Water Content in a Steep Forested Catchment

Abstract: Surface topography is commonly used as a proxy for soil water availability (Swetnam et al., 2017). This stems from our classic understanding that soil water is redistributed and organized in space via lateral and downslope movement. This can occur as saturation-excess surface runoff (Grayson et al., 1997; or as subsurface flow along a bedrock-soil interface or an interface between soil horizons (Lin et al., 2006). Consequently, terrain-based wetness metrics are widely used to identify likely runoff flow paths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 94 publications
0
11
0
Order By: Relevance
“…In contrast, hillslopes in WS1 are steep as are longitudinal valley gradients, which support significant subsurface hillslope (McGuire & McDonnell, 2010) and down‐valley flow (Kasahara & Wondzell, 2003; Voltz et al, 2013; Ward et al, 2018). Field observations during storms and multi‐year monitoring of 11 hillslope wells located in a variety of topographic positions all confirm that saturation to the soil surface is exceedingly rare, even at the bases of large hillslope hollows near the valley floor (Jarecke et al, 2021). Taken together, the geomorphic structure of the catchment, the deep soils with high infiltration capacity underlain by relatively permeable and deeply weathered saprolite and or fractured bedrock (Gabrielli et al, 2012), observations from hillslope wells, and field observations during storms all indicate that saturation excess overland flow is neither a significant source of runoff nor a viable mechanism to mobilize DOC from hillslopes to the active channel.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, hillslopes in WS1 are steep as are longitudinal valley gradients, which support significant subsurface hillslope (McGuire & McDonnell, 2010) and down‐valley flow (Kasahara & Wondzell, 2003; Voltz et al, 2013; Ward et al, 2018). Field observations during storms and multi‐year monitoring of 11 hillslope wells located in a variety of topographic positions all confirm that saturation to the soil surface is exceedingly rare, even at the bases of large hillslope hollows near the valley floor (Jarecke et al, 2021). Taken together, the geomorphic structure of the catchment, the deep soils with high infiltration capacity underlain by relatively permeable and deeply weathered saprolite and or fractured bedrock (Gabrielli et al, 2012), observations from hillslope wells, and field observations during storms all indicate that saturation excess overland flow is neither a significant source of runoff nor a viable mechanism to mobilize DOC from hillslopes to the active channel.…”
Section: Discussionmentioning
confidence: 97%
“…Soils average about 2.0 m in depth across the basin (range <0.2 to >5.0 m), and in most locations are underlain by deeply weathered saprolite (Jarecke et al, 2021). Hillslope soils are well drained and saturation does not occur within 2 m of the soil surface at any time of year (Jarecke et al, 2021). Stream channels are steep, with longitudinal gradients of ~14% in the well network reach, and the length of the network expands and contracts with changes in stream discharge.…”
Section: Study Site and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have similarly found that soil moisture is decoupled from TWI at dry and wet extremes (Tenenbaum et al., 2006). Studies have shown that terrain wetness indices are not universally appropriate in some montane systems (e.g., Jarecke et al., 2021; Keppeler & Brown, 1998; Penna et al., 2009). For instance, at the HJ Andrews Experimental Forest in the Oregon Cascades, it was recently found that hillslope soil moisture was primarily a function of soil properties and not of hillslope topography (Jarecke et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that terrain wetness indices are not universally appropriate in some montane systems (e.g., Jarecke et al, 2021;Keppeler & Brown, 1998;Penna et al, 2009). For instance, at the HJ Andrews Experimental Forest in the Oregon Cascades, it was recently found that hillslope soil moisture was primarily a function of soil properties and not of hillslope topography (Jarecke et al, 2021). Similarly, Penna et al (2009) found terrain indices alone to be poor predictors in spatial patterns of soil moisture.…”
Section: Wet Ridgesmentioning
confidence: 99%